Leisure, Social Networking and Mass Media: The Evolving Confluence - S., Satya (Indian Journal of Marketing, 2012)
Leisure is a versatile term; studies over the years have tried to define the term "leisure". It is clear from all the work undertaken that leisure is an "activity" and over the years, the nature of this activity has changed tremendously. Technology, and especially Information Communication Technology (ICT), has bought about a paradigm shift in leisure activities. Today, social networking has become the most important leisure activity also leveraging on other aspects like business, social causes to name a few. Social networking is getting to become one of the most popular mass media tools ever. The cost involved in reaching out to a focused target group amounts to nothing while bringing in the required 'action' and 'reaction'. Specific and focused lines of interest, congruence of peers, depth of expertise, spanning beyond time zones and geographic boundaries makes social networking gain an edge over the conventional mass media. Propagandas, which were spread through public speaking and personal charisma, can be done through social-networking today. Thus, social networking has taken over as an effective mass communication platform, blurring the significance of not only newspapers and televisions, but also personal propaganda.